1998
DOI: 10.1002/(sici)1521-3765(19980710)4:7<1305::aid-chem1305>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Directed Formation of Tetra-, Hexa-, Octa-, and Nonanuclear Complexes of Magnesium, Calcium, Manganese, Copper, and Cadmium

Abstract: Reactions of bis-1,3-dicarbonyl compounds H 2 L (1) with metal dichlorides of cadmium, manganese and calcium in the presence of aqueous ammonia affords octanuclear supramolecular coordination complexes [M 8 L 8 ]´4 Y (2 ± 5), whereas reaction with magnesium dichloride yields an adamantanoid tetranuclear cluster [(4 NH 4 ) (Mg 4 L a 6 )] (6). Treatment of copper dichloride with diethyl ketipinate 1 a and sodium hydroxide furnishes the double-/triple-decker metallacoronates [{[Na & (Cu 3 L a 3 )BF 4 ]´THFH 2 O} … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
6

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 6 publications
1
20
0
6
Order By: Relevance
“…329 The replacement of the R group in the tetracarboxylate ligand (Scheme 77) with hydrogen results in isosturctural homochiral ΔΔΔΔ and ΛΛΛΛ assemblies. 479 Variable-temperature 1 H NMR studies revealed that the assembly undergoes nondissociative enantiomerization from ΔΔΔΔ to ΛΛΛΛ symmetry without the formation of diastereomeric intermediates. 480 The interconversion involves four simultaneous Bailar twists associated with (Δ)/(Λ) isomerization at the four octahedral metal centers that are synchronized with the atropenantiomerization process on the four sterically unhindered ligands.…”
Section: Three Dimensional (3d) Nanoscopic Cagesmentioning
confidence: 99%
“…329 The replacement of the R group in the tetracarboxylate ligand (Scheme 77) with hydrogen results in isosturctural homochiral ΔΔΔΔ and ΛΛΛΛ assemblies. 479 Variable-temperature 1 H NMR studies revealed that the assembly undergoes nondissociative enantiomerization from ΔΔΔΔ to ΛΛΛΛ symmetry without the formation of diastereomeric intermediates. 480 The interconversion involves four simultaneous Bailar twists associated with (Δ)/(Λ) isomerization at the four octahedral metal centers that are synchronized with the atropenantiomerization process on the four sterically unhindered ligands.…”
Section: Three Dimensional (3d) Nanoscopic Cagesmentioning
confidence: 99%
“…Doppelte Deprotonierung des Diethylketipinsäureesters H 2 L 1 mit Natriumhydroxid in Gegenwart von Natriumtetrafluoroborat und Reaktion des gebildeten Dianions (L 1 ) 2− mit Kupfer(II)‐chlorid liefert hingegen das Metallocoronatdimer [{(Na⊂{Cu 3 (L 1 ) 3 })BF 4 } 2 ] ( 8 ) (Schema , Abbildung 4). 6b Das Monomer von 8 setzt sich zusammen aus dem Metallocoronandgrundgerüst {Cu 3 (L 1 ) 3 } mit einem Natriumion im Zentrum und einem BF 4 − als Gegenion. Die Verknüpfung der beiden Monomere zum Doppeldecker 8 erfolgt über die zwei Na + ‐Ionen zu einem Ringsauerstoffatom des benachbarten Coronats.…”
Section: Kationenunterstützte Bildung Von Metallocoronatenunclassified
“…Bei Abwesenheit von koordinierendem Wasser entsteht jedoch das Tripeldecker‐Metallocoronat [{(Na⊂{Cu 3 (L 1 ) 3 })BF 4 } 3 ] ( 9 ) (Schema , Abbildung 5). 6b…”
Section: Kationenunterstützte Bildung Von Metallocoronatenunclassified
See 1 more Smart Citation
“…[1] Die sorgfältige Auswahl geeigneter Liganden und Metallionen ermöglicht den gezielten Aufbau von Clustern mit definierter Geometrie und speziellen Eigenschaften. [3] [14] Mit dem Curtin-Hammett-Prinzip lässt sich auch der weit reichende Ladungstransport in den Experimenten von Schuster [2] und Barton et al [1] erklären. [2] b-Alaninhydroxamsäure und Salicylhydroxamsäure reagieren mit geeigneten Metallionen unter Bildung vierkerniger Metallacoronate.…”
unclassified